Politics and Society under the Bolsheviks
XVIII, 302 p.
Keywords: The relationship between society and the regime has been central to much recent research in the field of Soviet history. In this book, an international team of scholars investigates this theme in the revolutionary period, and in the Stalin years from the 1920s to the 1940s, with an additional section on the Bolshevik's relations with the outside world via the Communist International based in Moscow. The use of fresh archival materials provides challenging new interpretations and insights.